2010
DOI: 10.1017/s0007114510002333
|View full text |Cite
|
Sign up to set email alerts
|

Both high and low serum vitamin D concentrations are associated with tuberculosis: a case–control study in Greenland

Abstract: Vitamin D deficiency has been associated with increased risk of tuberculosis (TB). Changes from a traditional to a Westernised diet among Greenlanders have resulted in reduced serum vitamin D, leading to considerations of whether preventive vitamin D supplementation should be introduced. The association between vitamin D status and TB was examined to assess the feasibility of vitamin D supplementation in Greenland. This was examined in a case -control study involving seventy-two matched pairs of TB patients (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 19 publications
2
72
0
Order By: Relevance
“…On the other hand, there have been reports suggesting that vitamin D deficiency may cause anergy in the delayed hypersensitivity skin test in humans (28). Another study suggested that vitamin D supplementation may be beneficial to individuals with insufficient vitamin D concentrations but may increase the risk of tuberculosis among individuals with normal or high concentrations (29).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there have been reports suggesting that vitamin D deficiency may cause anergy in the delayed hypersensitivity skin test in humans (28). Another study suggested that vitamin D supplementation may be beneficial to individuals with insufficient vitamin D concentrations but may increase the risk of tuberculosis among individuals with normal or high concentrations (29).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, eleven case-control studies investigating the association between vitamin D status and susceptibility to active TB have been published. Of these, seven have reported a statistically significant association between vitamin D deficiency and susceptibility to active TB (34)(35)(36)(37)(38)(39)(40) , three have reported a non-statistically significant trend towards such an association (41)(42)(43) and one (44) has reported that active TB was associated with both 'high' and 'low' serum 25(OH)D concentrations (> 140 and < 75 nmol/l, respectively). Potential explanations for an association between vitamin D deficiency and active TB include both causality (i.e.…”
Section: Association Between Vitamin D Deficiency and Susceptibility mentioning
confidence: 99%
“…136 Despite these early promising results-plus the ability of vitamin D to increase that in addition to low vitamin D levels, excessive 25(OH)D levels may also increase the risk of tuberculosis. 144 A recently published randomized controlled trial demonstrated that the administration of four doses of 2.5 mg vitamin D(3) increased serum 25-hydroxyvitamin D concentrations in patients receiving intensive-phase treatment for pulmonary tuberculosis. Vitamin D significantly hastened sputum culture conversion in participants with the tt genotype of the TaqI vitamin D receptor polymorphism.…”
mentioning
confidence: 99%